Enrichment of a PHA producing microbial community in a continuous bioreactor setup - Valente, Raquel Sofia Corredoura (2014)
Polyhydroxyalkanoates (PHAs) are biosynthetic polyesters, biodegradable and biocompatible making them of great interest for industrial purposes. The use of low value substrates with mixed microbial communities (MMC) is a strategy currently used to decrease the elevated PHA production costs. PHA production process requires an important step for selection and enrichment of PHA-storing microorganisms which is usually carried out in a Sequencing Batch Reactor (SBR). The aim of this study was to optimize the PHA accumulating culture selection stage using a 2-stage Continuous Stirrer Tank Reactor (CSTR) system. The system was composed by two separate feast and famine bioreactors operated continuously, mimicking the feast and famine phases in a SBR system. Acetate was used as carbon source and biomass seed was highly enriched in Plasticicumulans acidivorans obtained from activated sludge. The system was operated under two different sets of conditions (setup 1 and 2), maintaining a system total retention time of 12 hours and an OLR of 2.25 Cmmol/L.h-1. An average PHB-content of 3.3 % wt was obtained in setup 1 and 4.8% wt in setup 2. Several other experiments were performed in order to better understand the continuous system behaviour, using biomass from the continuous system. With the fed-batch experiment a maximum of 8.1% PHB was stored and the maximum substrate uptake and specific growth rates obtained in the growth experiment (1.15 Cmol Cmol-1.h-1 and 0.53 Cmol Cmol-1.h-1) were close to the ones from continuous system (1.12 Cmol Cmol-1.h-1 and 0.59 Cmol Cmol-1.h-1). The microbial community was characterized trough microscopic visualization, Denaturing Gradient Gel Electrophoresis (DGGE) analysis and Fluorescent in situ hybridization (FISH). The last studied performed mimicked the continuous system by building up a SBR system with all the same operational conditions while adding an extra acetate dosage during the 12 h cycle, simulating the substrate passing from the feast to the famine reactors under continuous operation. It was shown that possibly the continuous system was not able to efficiently select for PHB storing organisms under the operational conditions imposed, although the selected culture was capable of consuming the substrate and grow fast. This main conclusion might have resulted from two major factors affecting the system performance: the ammonium concentration in the Feast reactor and the amount of substrate leaching from the Feast to the Famine reactor.